Dynamics of inflammatory changes of the gastric mucosa in children with duodenal ulcer - T.V. Sorokman; P.M. Moldovan; L.Yu. Khlunovska; I.Ya. Lozyuk (Zaslavsky O.Yu., 2021)
Background. The problem of gastrointestinal diseases in children remains quite relevant due to the high prevalence and presence of atypical symptoms and comorbidities pathogenetically associated with acid-dependent diseases. The purpose was to study the dynamics of inflammatory changes of the mucous membrane in children with duodenal ulcer (DU). Materials and methods. One hundred and six children aged 10 to 18 years with DU were examined. To verify the diagnosis, all children underwent endoscopy, pH-metry, morphological examination of gastrobiopsy samples, examination for Helicobacter pylori (H.pylori). Results. 49.1 % of children with DU were diagnosed with impaired motor-evacuatory function in the form of duodenogastric and/or gastrooesophageal reflexes, 81.1 % of patients presented with H.pylori was determined. Erythematous changes of the gastric and duodenal mucosa predominated. 92.4 % of patients were diagnosed with chronic non-atrophic gastritis and/or gastroduodenitis with varying degrees of inflammation, 7.6 % of children - chronic atrophic gastritis. There was a decrease in height and signs of desquamation of the superficial epithelium, in 72.3 % - the development of granular dystrophy, in 6.9 % of patients without H.pylori infection and in 57.5 % of H.pylori infected - neutrophilic infiltration of the mucous membrane. In the dynamics after 3 months, the height of the superficial epithelium and the frequency of desquamative changes decreased, and the proliferation of the glandular epithelium 12.4 % increased. Conclusions. Morphological changes in biopsies of the gastric mucosa differ depending on the presence of H.pylori infection and partially persist for 3 months after treatment.